(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Bimetallic nanoparticles (BNPs) have gained significant attention in the field of biomedical and pharmaceutical because of its tunable size, shape, high surface to volume and enhanced biological properties. In this study, we report the ecofriendly route to produce the noble (Ag-Au) bimetallic nanoparticles using aqueous flower extract of Clitoria ternatea as a reducing and capping agent. The synthesized C.T-Ag-Au BNPs were characterized by using physicochemical techniques such as UV-visible, FTIR, XRD and SEM-EDX analysis. The UV-visible spectra reveal the formation of homogeneous bimetallic nanoparticles by the single blue-shifted peak at 541 nm of C.T-Ag-Au BNPs. The phyto fabrication of synthesized C.T-Ag-Au BNPs was analyzed using FTIR spectroscopy. XRD confirms the formation of phase pure cubic Ag-Au alloy bimetallic nanoparticles with crystallite size is 14.5 nm. The surface morphology and elemental analysis of C.T-Ag-Au BNPs were examined by using SEM-EDX analysis. The synthesized C.TAg-Au BNPs were evaluated for their cytotoxicity against A549 human lung cancer cells through standard MTT assay. From this assay, green synthesized bimetallic nanoparticles induced cell apoptosis, suggesting that the synthesized C.T-Ag-Au BNPs gave best anticancer properties against lung cancer A549 cell lines.